Strategi Pengenalan Mata Uang melalui Fun Learning dalam Meningkatkan Minat Belajar pada Anak-anak Usia Dini - Mada, Qonita Al; Efendi, Rofik; Yuliani, Yuliani; Natalina, Sri Anugrah (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This service aims to increase young children's interest in learning about currency through the Fun Learning English approach. English Class is implemented with an interesting learning model, utilizing games and singing media to create a fun learning experience. The service method used is service learning, which involves direct interaction with children and the application of English knowledge in everyday contexts. The results of this service include increasing children's interest in learning, their understanding of currency, and the development of English language skills. With an innovative approach and involving fun learning elements, it is hoped that children can more easily understand the concept of currency through a fun and interactive learning experience.